Apogossypolone induces apoptosis and autophagy in nasopharyngeal carcinoma cells in an in vitro and in vivo study - Zheng, Ruinian (Oncol Lett, 2017)
Nasopharyngeal carcinoma (NPC) has a high incidence and mortality rate, particularly in Southern China. Apogossypolone (ApoG2) is a novel derivative of gossypol with antitumor activity and less toxicity. The human NPC CNE-2 cell line was studied in the in vitro model; whilst 4 week-old male nude mice (BALB/c-nu) were inoculated subcutaneously with CNE-2 cells, and xenograft tumors were studied in the in vivo model. Graded concentrations of ApoG2 were used in treatment studies. In ApoG2-treated and control in vitro and in vivo tumor cells, cell apoptosis, and autophagy were evaluated and quantified using fluorescent and transmission electron microscopy and flow cytometry. Hoechst-33258 fluorescence staining was used to evaluate apoptosis in treated and non-treated cell culture and xenograft NPC cells. Western blotting was performed on lysed tumor cells using primary antibodies to B-cell lymphoma-2 (Bcl-2), beclin-1, and β-actin, and flow cytometry results indicated cell apoptosis rates of 3.90±0.34 and 19.52±1.18% in the control and ApoG2-treated cells, respectively (F=485.294, P<0.001). Western blot analysis showed that ApoG2 significantly decreased expression of the Bcl-2 protein in CNE-2 cells, when compared with control cells (F=68.909, P=0.001) and flow cytometry showed cell autophagy rates of 0.92±3.10% of control cells compared with 28.24±7.35% of ApoG2-treated cells (F=31.035, P=0.003). ApoG2 treatment significantly increased beclin-1 protein expression in CNE-2 cells (F=497.906, P<0.001). ApoG2 treatment inhibited NPC xenograft tumor growth by 65.49% (P<0.05). In conclusion, these results support a role for ApoG2 in inhibiting the growth of human NPC cells by inducing apoptosis and autophagy. Future controlled clinical studies could be planned, to define safety, efficacy and dosing regimens for ApoG2 as a potential treatment for patients with NPC.